The Dominican Stance on the Immaculate Conception of Mary: Insights from Selected Sermons (13th–15th Centuries) - Kochaniewicz, Bogusław (Verbum vitae, 2024)
It is commonly believed that in the debate on the Immaculate Conception of the Blessed Virgin Mary, representatives of the Order of St. Francis were supporters of the Marian privilege, while the Dominicans were against it. The aim of this article is to verify this opinion by analyzing selected Dominican homilies from the 13th -15th centuries, seeking answers to the questions: has the maculist position expressed by preachers been maintained over the centuries? What caused Dominicans to remain unchanged in their views, despite the gradual spread of the opinion about the Immaculate Conception of Mary, which was finally officially accepted by the Church? What role did Saint’s opinion play? Thomas Aquinas to the position of later Dominicans? The results of the analysis of medieval Dominican sermons allow us to consider the opinion that has so far been widespread as one-sided and superficial. The Dominican position is much more complex.